Features of Modern Design of Steel Crane Beams for Industrial Buildings - Radkevych, A. V.; Bannikov, D. O.; Chen, S. P.; Fu, X. F. (Science and Transport Progress, 2025)
Purpose. The main purpose of the publication is to comprehensively compare the methods and approaches to the design of steel crane beams according to the current standards of China and Ukraine. The relevance of the work is due to the constant increase in the volume and types of cooperation between these two countries over the past decades. The subject matter is also related to the increasing use of high-strength steels in construction practice, which also have a number of additional improved performance characteristics. Methodology. To achieve this goal, we considered the design of a 6 m span steel simply supported crane beam at one of the modern energy enterprises in Ukraine. The load was assumed to come from an electric overhead crane with a lifting capacity of 25 tones. The selected cross-section was checked in accordance with the design requirements of the current standards of China and Ukraine, which together include about 20 items. Separate consideration was given to the design requirements for the arrangement of reinforcing stiffeners and ensuring local stability of the section elements. Findings. The comparative analysis of the existing approaches according to the standards of China and Ukraine has made it possible to establish that, in general, the Chinese standard imposes more stringent requirements both for the material to be used for the crane beam production and for design and construction solutions. At the same time, in terms of ensuring general and local stability, the Chinese standard uses a fundamentally different conceptual approach than the Ukrainian standard. However, the final solution has approximately the same level of bearing capacity. Originality. The comparative analysis of the requirements of the current Chinese and Ukrainian standards for the design of steel crane beams has made it possible to identify the strengths and weaknesses of each standard, as well as to outline the main fundamental differences between them. Practical value. The paper develops and proposes for practical implementation a design variant of a steel simply supported crane beam, which in terms of its bearing capacity meets the requirements of the current standards of China and Ukraine in the field of metal construction.